2016
DOI: 10.1016/j.micromeso.2016.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Porosity and thickness characterization of porous Si and oxidized porous Si layers – An ultraviolet–visible–mid infrared ellipsometry study

Abstract: +3620 361 7876This paper suggests the evaluation of morphological parameters of porous silicon layers (PSL) using spectroscopic ellipsometry from UV to midinfrared optical range. PSL were prepared by electrochemical etching of monocrystalline silicon wafers in hydrofluoric acid-based electrolyte. Measuring with an optical and an infrared ellipsometer with a wide spectral range permits an accurate characterization of PSL properties from the top surface to the bottom of the layer with thicknesses from several hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…2, the increase of porosity and thickness of the porous layer with etching time from 2 to 4 min as illustrated in Table 1. That agrees with Fodora et al reported that the average porosity increases rapidly with thickness silicon [9]. Etching rate or growth rate data of the porous silicon measured by Eq.…”
Section: Resultssupporting
confidence: 91%
“…2, the increase of porosity and thickness of the porous layer with etching time from 2 to 4 min as illustrated in Table 1. That agrees with Fodora et al reported that the average porosity increases rapidly with thickness silicon [9]. Etching rate or growth rate data of the porous silicon measured by Eq.…”
Section: Resultssupporting
confidence: 91%
“…As the samples were thermally oxidized, it is likely that the pores were closed on the upper layer, which prevents the diffusion of oxygen to the remaining silicon [18]. For this reason, two volume fractions (SiO 2 and c-Si) were used in the Looyenga EMA model.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal oxidation forms an SiO 2 layer on the sample surface. We suppose that the pores were closed in the upper sublayers, which prevents the diffusion of oxygen to the remaining structure [4]. This process is illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…B-Si is a sponge-like structure of monocrystalline silicon, which became one of the most well-researched silicon structures [3]. B-Si has a wide range of industrial applications (as sensors, as anodes in Lithium-ion battery, photovoltaic applications, biosensors, optoelectronics, self-cleaning coatings, etc) [3][4][5]. This paper deals with applications of b-Si in solar cells.…”
Section: Introductionmentioning
confidence: 99%